2(2-7x)=-52

Simple and best practice solution for 2(2-7x)=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2-7x)=-52 equation:


Simplifying
2(2 + -7x) = -52
(2 * 2 + -7x * 2) = -52
(4 + -14x) = -52

Solving
4 + -14x = -52

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -14x = -52 + -4

Combine like terms: 4 + -4 = 0
0 + -14x = -52 + -4
-14x = -52 + -4

Combine like terms: -52 + -4 = -56
-14x = -56

Divide each side by '-14'.
x = 4

Simplifying
x = 4

See similar equations:

| 10=2x-5+5 | | 1470-2x= | | 6c-5d=-8 | | 2y+3=2(y+3) | | 120=118 | | 12x+9=9x+45 | | -45+18=-4x+13x | | 2(4-3.5y)=22.5 | | 7(x-35)=5x | | 15b^2+6b=4b+10b^2+14 | | 4x-2(x-2)=-4+5x-10 | | 24-6x=10+8x | | x-(-14)=-2 | | -0.004*4.2= | | -6(7x-5)=72 | | (4b^9)= | | x+log(x)=0 | | 8x+17-7x=-3-12 | | 3.6+(-0.6)= | | x+(-3)=-3 | | 3.6+(-6.5)= | | 55=x^2*3.14 | | 53y=13(4y+30) | | 28+24x=42+17m | | 45=x^2*3.14 | | 5k+3-3k=6k | | -6(3+7x)=-438 | | xy+y=x | | 7(35x)=5x | | 35=x^2*3.14 | | 3(3x-9)=9 | | 1.63-0.9= |

Equations solver categories